Analysis of Sea Turtle Nesting Area in Pandan Island West Sumatra - Turnip, Masnawita; Nasution, Syafruddin; Galib, Musrifin (Jurnal Perikanan dan Kelautan, 2020)
The research was conducted on February – March 2020 and located in Pandan Island with using survey method. The research aimed to analyze characteristic habitat of the physical and biological turtle nesting beaches, the distribution of turtle’s nests, and the microbial conditions of the turtle’s nests. The result showed that the length of beach was 1,379.4 m with average width of beach was 16.13 m. The average beach slope was 5.52 %. Substrate type dominated by sand substrate. The most abundant vegetation was ketapang tree (Terminalia catappa) and the predators discovered were monitor lizard and dog. There where 4 turtle nests were found, which was 3 nests of hawksbill turtles and 1 nest of green turtle. The average distance of nests from high tide line was 5.7 m with average distance between nest was 177.87 m. Respectively, the average of temperature, humidity, and depth of the nests were 29.58℃, 12.78%, and 53.3 cm. The average size of curve carapace length was 84.25 cm and average curve carapace width was 76.25 cm. The average number of eggs was 144 of each nest with average diameter of eggs was 3.35 cm